PERAN BELANJA DAERAH SEBAGAI KATALISATOR DAYA SAING DAERAH - Kustiani, Aisyah; Hadi, Miftahul; Mahrus, Muhammad Luthfi (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to examine the effect of regional spending on regional competitiveness. The study was conducted using a quantitative approach with panel data regression. The sample used in this study consisted of 503 regencies and cities in Indonesia with an observation period of two years (2022-2023). The dependent variable in this study was regional competitiveness, which was measured using the regional competitiveness index. The independent variables in this study are regional spending, mandatory spending (spending on education and health), economic spending, and environmental spending. The results show that total regional spending and economic spending have no significant effect. Mandatory spending has a significant effect but with a relationship that is opposite to what was expected. Environmental function spending has a positive and statistically significant effect. The results of this study indicate that government spending will serve as a catalyst for regional competitiveness, but the accuracy of its allocation needs to be analyzed. Local governments need to reprioritize budget allocations in sectors that encourage regional competitiveness. In addition, efforts need to be made to increase the effectiveness of mandatory spending (education, health, and infrastructure) and strengthen institutional capacity to avoid high budget expenditures that do not result in increased regional competitiveness. Furthermore, government spending requires a long time to have an impact on regional competitiveness. Keywords: regional competitiveness, accounting, government, spending, environment